Risk factors for dental erosion in 5–6 year old and 12–14 year old boys in Saudi Arabia - Al-Majed I, Maguire A, Murray JJ. (Blackwell Synergy, 2002)
Dental examinations were carried out on 354 boys aged 5–6 years, and 862 boys aged 12–14 years, attending 40 schools in Riyadh. The prevalence of dental erosion was assessed using diagnostic criteria similar to those employed in the 1993 UK National Survey of Child Dental Health.